2015
DOI: 10.1042/bj20150744
|View full text |Cite
|
Sign up to set email alerts
|

The sequence Pro295–Thr311 of the hinge region of oestrogen receptor α is involved in ERK1/2 activation via GPR30 in leiomyoma cells

Abstract: The ERα (oestrogen receptor α)-derived peptide ERα17p activates rapid signalling events in breast carcinoma cells under steroid-deprived conditions. In the present study, we investigated its effects in ELT3 leiomyoma cells under similar conditions. We show that it activates ERK1/2 (extracellular-signal-regulated kinase 1/2), the Gαi protein, the trans-activation of EGFR (epidermal growth factor receptor) and, finally, cell proliferation. It is partially internalized in cells and induces membrane translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 62 publications
2
27
0
Order By: Relevance
“…Additionally, blockade of both ERα and ERβ in an isolated perfused heart attenuated G-1-mediated changes in heart rate and left ventricular pressure (Filice et al, 2009). In another study, blockade of GPER-1 attenuated the ability of the ERα-derived peptide, ERα17p, to activate ERK1/2 in leiomyoma cells (Leiber et al, 2015). Even fewer studies have investigated the potential cross talk between GPER-1 and ERα in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, blockade of both ERα and ERβ in an isolated perfused heart attenuated G-1-mediated changes in heart rate and left ventricular pressure (Filice et al, 2009). In another study, blockade of GPER-1 attenuated the ability of the ERα-derived peptide, ERα17p, to activate ERK1/2 in leiomyoma cells (Leiber et al, 2015). Even fewer studies have investigated the potential cross talk between GPER-1 and ERα in the brain.…”
Section: Discussionmentioning
confidence: 97%
“…Strikingly, ERα17p aggregates induce membrane invaginations, an observation that could be related to an entry mechanism ( Figure 4B) [51]. Accordingly, it has been demonstrated that the peptide ERα17p was internalized, even though weakly, in leiomyoma cells (Elt3) and after 75 min incubation (5.5 ± 1.8 pmol/250,000 cells) [14]. In CHO cells and under similar experimental conditions, it is marginally internalized (0.3 ± 0.1 pmol/10 6 cells) [25].…”
Section: Sem and Tem Experimentsmentioning
confidence: 81%
“…5(6)-carboxyfluorescein was purchased from Sigma-Aldrich (Saint-Quentin Fallavier, France). The peptide ERα17p was obtained and characterized as previously described [14,25]. MCF-7 breast cancer cells were cultured in growth Dulbecco's Modified Eagle Medium DMEM (ThermoFisher Scientific, Courtaboeuf, France) supplemented with fetal calf serum (FCS), penicillin/streptomycin (100,000 IU/L), and amphotericin B (1 mg/L), in a humidified atmosphere containing 5% CO 2 at 37 • C.…”
Section: Materials and Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations